Association of GSTT1 and GSTM1 gene polymorphisms with coronary artery disease in North Indian Punjabi population: a case-control study. Issue 1094 (23rd May 2016) - Bhat, Mohd Akbar; Gandhi, Gursatej
Abstract: Background: Glutathione S-transferases are metabolic enzymes which are responsible for detoxification of endogenous (products of oxidative stress) as well as exogenous (drugs, pesticides, herbicides, environmental pollutants and carcinogens) products. Dysfunctional detoxification enzymes are responsible for the production of oxidative stress; a major contributor to the development of coronary artery disease (CAD). Objectives: The present case-control study aimed to investigate the association of GSTT1 and GSTM1 gene polymorphisms with CAD. Methods: In the present study, 200 patients diagnosed with CAD and 200 age, sex and population subgroup matched healthy controls were enrolled. The GSTT1 and GSTM1 gene polymorphisms were examined using multiplex PCR. Results: The frequency of GSTT1 null genotype was significantly (p=0.038) lower in patients with CAD (6.00%) than in controls (12.50%). The GSTT1 null genotype showed protection against CAD (OR=0.45, 95% CI 0.22 to 0.92, p=0.028). The frequency of GSTM1 null genotype was significantly (p=0.004) higher in patients (31%) compared with controls (18%). The GSTM1 null genotype conferred twofold increased risk of developing CAD (OR=2.05, 95% CI 1.28 to 3.27, p=0.003). Conclusions: The results concluded that the GSTT1 null genotype showed protection against CAD while the GSTM1 null genotype might be involved in the pathogenesis and development of CAD.